1985
DOI: 10.1002/j.1537-2197.1985.tb08327.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Aluminum Tolerance in Triticum Aestivum L. (Wheat). I. Differential Ph Induced by Winter Cultivars in Nutrient Solutions

Abstract: Twenty winter cultivars of Triticum aestivum L. (wheat) were grown in solution culture with and without aluminum (Al) (74 μM, 2.0 mg L‐1) for 14 days. Exposure to Al increased root growth of the most tolerant cultivar, while both root and shoot growth were depressed in all other cultivars. On the basis of a root tolerance index (RTI = weight of roots grown with Al/weight of roots grown without Al), cultivar tolerance to Al ranged 9‐fold, from 0.13 ± 0.01 to 1.16 ± 0.10. Symptoms of Al toxicity were most eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Several authors [13,[143][144][145][146][147] have shown that the tolerance to soil acidity and Al toxicity in certain species or genotypes was related to their ability to take up H ϩ and thereby to increase rhizosphere pH. Indeed, aluminum is a toxic element that severely limits growth at pH below 5.0 as a consequence of its pH-dependent speciation and the considerable increase in the solubility of aluminum-bearing minerals with decreasing pH.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors [13,[143][144][145][146][147] have shown that the tolerance to soil acidity and Al toxicity in certain species or genotypes was related to their ability to take up H ϩ and thereby to increase rhizosphere pH. Indeed, aluminum is a toxic element that severely limits growth at pH below 5.0 as a consequence of its pH-dependent speciation and the considerable increase in the solubility of aluminum-bearing minerals with decreasing pH.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, however, Taylor (1988) demonstrated that the superior Al tolerance of Atlas-66 was not related to its ability to maintain a high solution pH by NO 3 − uptake. Glutamine synthetase Taylor and Foy, 1985a, 1985b, 1985c *Decrease for some genotypes but not for other genotypes. (The relationship between Al tolerance and medium pH is discussed in detail later.)…”
Section: The Aluminum-nitrogen Interactionmentioning
confidence: 98%
“…Thus, it is logical to expect that plants will be more Al tolerant growing on NO 3 − -containing medium than on NH 4 + -containing medium (Taylor and Foy, 1985a, 1985b, 1985c. In general, NH 4 + predominates in acidic soils because of their low nitrification rates, whereas NO 3 − is the main form of N in neutral and calcareous soils.…”
Section: The Aluminum-nitrogen Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of Al toxicity in wheat (Triticum aestivum L.) were relatively short and thick roots with numerous undeveloped laterals (Taylor and Foy, 1985). Aluminium toxicity symptoms were also observed in tropical leguminous plants, for example darkening, shrinking and inhibition of lateral root growth two days after transplanting (Meda and Furlani, 2005).…”
Section: Effects On Plant Growthmentioning
confidence: 99%